A multi-stakeholder view on director remuneration guidance in South Africa. (2nd September 2022) - van Zyl, Marilee; Mans-Kemp, Nadia
Abstract : Purpose: Given South Africa's well-developed governance framework, considerable wage inequality and sizeable executive packages, this study was conducted to reflect on the aptness and application of the King IV director remuneration guidelines. Design: The views of 23 representatives of institutional investors, remuneration committee members and leading executives of financial services companies were gauged on the King IV remuneration recommendations by conducting semi-structured interviews. The primary data were analysed by conducting thematic analysis. Findings: The participants commended the heightened focus on pay-related transparency and reporting quality evident in King IV, in particular the three-part remuneration report and single pay figure disclosure. Participants urged remuneration committees to link executive pay to the six capitals. Practical implications: Government and the Institute of Directors in South Africa should account for the considerable regulatory burden that companies are experiencing when amending remuneration-related regulation in future. More guidance is required to link sustainability considerations to executive emolument. A corporate culture which promotes fair remuneration would benefit multiple stakeholders. Focus should be placed on equal pay for work of equal value. Value: The views of powerful and informed stakeholder representatives were gauged on responsible and transparent remuneration practices in an emerging market with severe pay inequality.